Early Markers of Cardiovascular Risk in Autosomal Dominant Polycystic Kidney Disease - Silvia Lai; Daniela Mastroluca; Silvia Matino; Valeria Panebianco; Antonio Vitarelli; Lidia Capotosto; Irene Turinese; Paolo Marinelli; Marco Rossetti; Alessandro Galani; Pia Baiocchi; Anna R. D'Angelo; et al. (Karger Publishers, 2017)
Background/Aims: Cardiovascular disease is the most frequent cause of morbidity and mortality in autosomal dominant polycystic kidney disease (ADPKD) patients, often before the onset of renal failure, and the pathogenetic mechanism is not yet well elucidated. The aim of the study was to identify early and noninvasive markers of cardiovascular risk in young ADPKD patients, in the early stages of disease. Methods: A total of 26 patients with ADPKD and 24 control group, matched for age and sex, were enrolled, and we have assessed inflammatory indexes, mineral metabolism, metabolic state and markers of atherosclerosis and endothelial dysfunction (carotid intima media thickness (IMT), ankle brachial index (ABI), flow mediated dilation (FMD), renal resistive index (RRI), left ventricular mass index (LVMI)) and cardiopulmonary exercise testing (CPET), maximal O2 uptake (V'O2max), and O2 uptake at lactic acid threshold (V'O2@LT). Results: The ADPKD patients compared to control group, showed a significant higher mean value of LVMI, RRI, homocysteine (Hcy), Homeostasis Model Assessment-insulin resistance (HOMA-IR), serum uric acid (SUA), Cardiac-troponinT (cTnT) and intact parathyroid hormone (iPTH) (p<0.001, p<0.001, p<0.001, p<0.001, p<0.001, p=0.007, p=0.019; respectively), and a lower value of FMD and 25-hydroxyvitaminD (25-OH-VitD) (p<0.001, p<0.001) with reduced parameters of exercise tolerance, as V'O2max, V'O2max/Kg and V'O2max (% predicted) (p<0.001, p<0.001, p=0.018; respectively), and metabolic response indexes (V'O2@LT, V'O2 @LT%, V'O2@LT/Kg,) (p<0.001, p=0.14, p<0.001; respectively). Moreover, inflammatory indexes were significantly higher in ADPKD patients, and we found a positive correlation between HOMA-IR and C-reactive protein (CRP) (r=0.507, p=0.008), and a negative correlation between HOMA-IR and 25-OH-VitD (r=-0.585, p=0.002). Conclusion: In our study, ADPKD patients, in the early stages of disease, showed a greater insulin resistance, endothelial dysfunction, inflammation and mineral metabolism disorders, respect to control group. Moreover, these patients presented reduced tolerance to stress, and decreased anaerobic threshold to CPET. Our results indicate a major and early cardiovascular risk in ADPKD patients. Therefore early and noninvasive markers of cardiovascular risk and CPET should be carried out, in ADPKD patients, in the early stages of disease, despite the cost implication.